PENGOLAHAN LIMBAH CAIR RUMAH POTONG HEWAN MENGGUNAKAN ROTATING BIOLOGICAL CONTACTOR MODIFIKASI SLUDGE ZONE - Hendrasarie, Novirina; Santosa, Bagas Aldin (2477 - 6165, 2019)
Slaughterhouse wastes generally contain blood, proteins, fats, and suspended solids that cause a high load of organic matter which can pollute rivers and water body. The waste water of slaughter house will cause changes on the quality of the water, such as increased colour, pH, total dissolved solids, suspended solids, fats, BOD5, ammonium, nitrogen and phosphor. In this study aims to reduce the content of slaughterhouse waste water, using Rotating Biological Contactor (RBC) modified with a sludge zone. It was expected that by modifying the sludge zone, the efficiency of RBC performance can be further improved. This study used a variety of Hydraulic Retention Time (HRT) of 2.8 hours, 3.5 hours and 4.2 hours along with waste water dilution of 50%, 75% and 100% using the continue system into clarifier process. Based on the results of the study, the decreased percentage in COD concentration reached 86.68%, the total decreased percentage of Nitrogen concentration reached 66.11% and the decreased percentage in TSS concentration reached 71.87%. The pH value is neutral with a range of 7.6-8.3 with temperatures range of 26oC-30oC during operation. The highest DO values reached 5.2 mg/L with a range of organic surface loading values of 89.77 - 135.45 grams BOD/m2 .day. The organic load figure exceeds the RBC organic load standard which averages around 8-20 grams/BOD/m2.day. The increased of organic load, indicates that RBC with modified sludge zone was able to treat wastewater with high organic load, such as slaughterhouse waste water.